Emerging role of lncRNAs in drug resistance mechanisms in head and neck squamous cell carcinoma - Peña-Flores, José A.; Bermúdez, Mercedes; Ramos-Payán, Rosalío; Villegas-Mercado, Carlos E.; Soto-Barreras, Uriel; Muela-Campos, Daniela; Álvarez-Ramírez, Alexis; Pérez-Aguirre, Brenda; Larrinua-Pacheco, Ana D.; López-Camarillo, César; López-Gutiérrez, Jorge A.; Garnica-Palazuelos, Julio; et al. (Frontiers in Oncology, 2022)
Head and Neck Squamous Cell Carcinoma (HNSCC) is originated in the squamous cell lining the mucosal surfaces of the head and neck region, including the oral cavity, nasopharynx, tonsils, oropharynx, larynx, and hypopharynx. The heterogeneity, anatomical, and functional characteristics make the HNSCC a complex and difficult-to-treat disease, leading patients to a poor survival rate and a decreased life quality due to loss of important physiologic functions and aggressive surgical injury. Alteration of driver-oncogenic and tumor-suppressing lncRNAs have been studied recently in HNSCC to obtain possible biomarkers for diagnostic, prognostic, and therapeutic approaches This review aims to provide current knowledge about the implication of lncRNAs in drug resistance mechanisms in HNSCC. Chemotherapy resistance is a major therapeutic challenge in HNSCC in which lncRNAs are implicated. Lately, it has been shown that lncRNAs involved in autophagy induced by chemotherapy and epithelial-mesenchymal transition (EMT) can act as mechanisms of resistance to anticancer drugs. Conversely, lncRNAs involved in mesenchymal-epithelial transition (MET) are related to chemosensitivity and inhibition of invasiveness of drug-resistant cells. In this regard, long non-coding RNAs (lncRNAs) play a pivotal role in both processes and are important for cancer detection, progression, diagnosis, therapy response, and prognostic values. As the involvement of more lncRNAs is elucidated in chemoresistance mechanisms, an improvement in diagnostic and prognostic tools could promote an advance in targeted and specific therapies in precision oncology.